2014
DOI: 10.17305/bjbms.2014.3.37
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Magnetic Resonance Imaging of Endoscopic Third Ventriculostomy Patency With Differently Acquired Fast Imaging With Steady-State Precission Sequences

Abstract: The aim of the study was to determine the possibilities of two differently acquired two-dimensional fast imaging with steady-state precession (FISP 2D) magnetic resonance sequences in estimation of the third ventricle floor fenestration patency after endoscopic third ventriculostomy (ETV) in the subjects with aqueductal stenosis/obstruction.Fifty eight subjects (37 males, 21 females, mean age 27 years) with previously successfully performed ETV underwent brain MRI on 1.5T MR imager 3-6 months after the procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…is was evidenced by the reduced aqueductal flow on cine MR images and consistent with the studies by Lucic et al, Parkkola et al, and Abdelhameed et al, wherein reduced aqueductal flow was observed in patients with hydrocephalus as a result of aqueductal stenosis. [19][20][21] is further affirms the role of PCMRI in the differentiation of communicating and non-communicating hydrocephalus.…”
Section: Discussionmentioning
confidence: 53%
“…is was evidenced by the reduced aqueductal flow on cine MR images and consistent with the studies by Lucic et al, Parkkola et al, and Abdelhameed et al, wherein reduced aqueductal flow was observed in patients with hydrocephalus as a result of aqueductal stenosis. [19][20][21] is further affirms the role of PCMRI in the differentiation of communicating and non-communicating hydrocephalus.…”
Section: Discussionmentioning
confidence: 53%
“…The mean Diameter 3r d ventricle in mm Preoperative was 9.92 (±1.14 SD) with range (7.9-12.4) and the mean Diameter 3 rd ventricle in mm Postoperative was 5.72 (±1.82 SD) with range (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). There was a high statistically significant difference between preoperative and postoperative Diameter 3 rd ventricle in mm, Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Our results are in agreement with (Qiguang Wang, Jian Ching, Si Zhang, Qiang Li, Xuhui Hui, Yun Ju) as they observed that all the patients underwent ballooning of the floor of the third ventricle, the most common etiologies were brain tumors and aqueduct stenosis. Lucic et al [11] showed "patients included in their study hospitalized for the treatment of obstructive hydrocephalus due to the non-tumorous stenosis/obstruction of cerebral aqueduct". Zohdi et al [12] reported that their patients had obstructive hydrocephalus due to congenital aqueductal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…On T2 that is performed postoperatively with the purpose of observing the ventricles or morphological changes in the cyst, CSF motion through the fenestration is observed as an artifact in addition to morphological information, albeit with mediocre visibility. 20,21) Imaging methods such as phase contrast (PC), [22][23][24] the time-spatial inversion pulse (Time-SLIP) method, 25) and two-dimensional fast imaging with steady-state precession magnetic resonance sequence 26) have been used for post-ETV evaluation as a superior method to visualize CSF motion. The Dynamic iMSDE SSFP method described in this manuscript is superior for visualizing the irregular CSF motions, and our results showed that fenestration of cyst or ventricle with limited CSF motion resulted in clear visualization of recovered CSF motion as a turbulent movement.…”
Section: Fig 3 Left: a 13-year-old Female Who Presented With Obstrucmentioning
confidence: 99%